Molecular Mechanisms of Oxygen Evolution Reactions for Artificial Photosynthesis - Yoshio Nosaka (Oxygen, 2023)
Addressing the global environmental problem of water splitting to produce hydrogen fuel by solar energy is receiving so much attention. In water splitting, the essential problem to solve is the development of efficient catalysts for oxygen production. In this paper, having the prospect for a practical application of photocatalysts to artificial photosynthesis, molecular mechanisms in the current literature are briefly reviewed. At first, recent progress in the function of the Mn cluster at the natural photosystem II is briefly described. The kinds of devices in which oxygen evolution reaction (OER) catalysts are used were designated: water electrolyzers, photoelectrodes, and photocatalysts. Some methods for analyzing molecular mechanisms in OER catalysis, emphasized by the FTIR method, are shown briefly. After describing common OER mechanisms, the molecular mechanisms are discussed for TiO2 and BiVO4 photoelectrodes with our novel data, followed by presenting OER co-catalysts of IrO2, RuO2, NiO2, and other metal oxides. Recent reports describing OER catalysts of perovskites, layered double hydroxides (LDH), metal–organic frameworks (MOF), single-atom catalysts, as well as metal complexes are reviewed. Finally, by comparing with natural photosystem, the required factors to improve the activity of the catalysts for artificial photosynthesis will be discussed.